2016
DOI: 10.1109/tit.2016.2527637
|View full text |Cite
|
Sign up to set email alerts
|

One-Bit Compressive Sensing With Norm Estimation

Abstract: Consider the recovery of an unknown signal x from quantized linear measurements. In the one-bit compressive sensing setting, one typically assumes that x is sparse, and that the measurements are of the form sign( a i , x ) ∈ {±1}. Since such measurements give no information on the norm of x, recovery methods typically assume that x 2 = 1. We show that if one allows more generally for quantized affine measurements of the form sign( a i , x + b i ), and if the vectors a i are random, an appropriate choice of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(121 citation statements)
references
References 35 publications
3
114
1
Order By: Relevance
“…There, it was shown that amplitude information about the transmitted signal can be recovered even in the presence of a single-bit quantizer, provided that the number of receive antennas is sufficiently large and the signalto-noise ratio (SNR) is not too high. The observation that noise can help recovering magnitude information under 1-bit quantization has also been made in the compressive-sensing literature [9], [10].…”
Section: B Relevant Prior Artmentioning
confidence: 79%
“…There, it was shown that amplitude information about the transmitted signal can be recovered even in the presence of a single-bit quantizer, provided that the number of receive antennas is sufficiently large and the signalto-noise ratio (SNR) is not too high. The observation that noise can help recovering magnitude information under 1-bit quantization has also been made in the compressive-sensing literature [9], [10].…”
Section: B Relevant Prior Artmentioning
confidence: 79%
“…A special technique within compressed sensing is the so-called "1-bit" compressed sensing [68][69][70], where 1-bit measurements are applied that preserve only the sign information of the measurements.…”
Section: Compressed Sensingmentioning
confidence: 99%
“…The thresholding step, namely the part where we take use V to filter out non-heavy intervals cannot be implemented here, but perhaps there is still a way to make a similar argument. One first approach should be to show that sublinear decoding with optimal measurements is achieved using non-adaptive threshold measurements, such as in [KSW16] and [BFN + 17] (note that the latter one uses adaptive measurements though).…”
Section: Possible Applications Of Our Approach To Other Problemsmentioning
confidence: 99%